Strategi Coping dalam Menghadapi Kematian Ibu pada Wanita Dewasa yang Mengalami Fatherless - Arhadita, Inocencia Vivinca; Darmawanti, Ira (Universitas Trunojoyo Madura, 2024)
The death of a mother brings deep mourning to a daughter, especially when faced without the presence of a father figure or fatherless. Its indirect effects pose their own challenges in navigating life after the loss of a mother. The importance of addressing grief by selecting appropriate strategies significantly influences how one continues their life. This research aims to understand the experiences of the subjects, who are early adult women, in facing life after the death of their mother, and to analyze the coping strategies used. In the context of this research, the case study method is employed to deeply understand the experiences and coping strategies of adult women in facing the death of a mother and fatherlessness. The research findings indicate that external and internal support, as well as the use of positive and negative coping strategies, have different impacts.